PENGARUH LEADER MEMBER EXCHANGE TERHADAP PERILAKU KERJA INOVATIF PEGAWAI DI LAPAS KELAS IIA PURWOKERTO - Hanifan, Addinulloh Achmad; Pangestuti, Naniek (Journal of Management Small and Medium Enterprises (SMEs), 2024)
This research aims to determine the influence of leader-member exchange on the innovative work behavior of Class IIA Purwokerto prison employees. The research method used is quantitative. The population in this study were all Purwokerto prison employees, where a purposive sampling technique using the Krejcie and Morgan method was used to obtain a sample of 92 employees. The results of this research show that leader-member exchange significantly influences the innovative work behavior of Class IIA Purwokerto prison employees. The results of the determination test show that leader-member exchange as an independent variable has a 13% effect on innovative work behavior as a dependent variable for Class IIA Purwokerto prison employees. Researchers expect that future research can add other variables as mediators which might increase the indirect influence of leader-member exchange on innovative work behavior. Keywords: Leader-Member Exchange; Innovative Work Behavior; Correctional